Clinical spectrum time course in non-Asian patients positive for anti-MDA5 antibodies. - Cavagna, L.; Meloni, F.; Meyer, A.; Sambataro, G.; Belliato, M.; De Langhe, E.; Cavazzana, I.; Pipitone, N.; Triantafyllias, K.; Mosca, M.; Barsotti, S.; Zampogna, G.; et al. (Clinical and Experimental Rheumatology, 2022)
OBJECTIVES: To define the clinical spectrum time-course and prognosis of non-Asian patients positive for anti-MDA5 antibodies. METHODS: We conducted a multicentre, international, retrospective cohort study. RESULTS: 149 anti-MDA5 positive patients (median onset age 53 years, median disease duration 18 months), mainly females (100, 67%), were included. Dermatomyositis (64, 43%) and amyopathic dermatomyositis (47, 31%), were the main diagnosis; 15 patients (10%) were classified as interstitial pneumonia with autoimmune features (IPAF) and 7 (5%) as rheumatoid arthritis. The main clinical findings observed were myositis (84, 56%), interstitial lung disease (ILD) (108, 78%), skin lesions (111, 74%), and arthritis (76, 51%). The onset of these manifestations was not concomitant in 74 cases (50%). Of note, 32 (21.5%) patients were admitted to the intensive care unit for rapidly progressive-ILD, which occurred in median 2 months from lung involvement detection, in the majority of cases (28, 19%) despite previous immunosuppressive treatment. One-third of patients (47, 32% each) was ANA and anti-ENA antibodies negative and a similar percentage was anti-Ro52 kDa antibodies positive. Non-specific interstitial pneumonia (65, 60%), organising pneumonia (23, 21%), and usual interstitial pneumonia-like pattern (14, 13%) were the main ILD patterns observed. Twenty-six patients died (17%), 19 (13%) had a rapidly progressive-ILD. CONCLUSIONS: The clinical spectrum of the anti-MDA5 antibodies-related disease is heterogeneous. Rapidly-progressive ILD deeply impacts the prognosis also in non-Asian patients, occurring early during the disease course. Anti-MDA5 antibody positivity should be considered even when baseline autoimmune screening is negative, anti-Ro52 kDa antibodies are positive, and radiology findings show a NSIP pattern.
EVALuna2:520821